Studying the relationship between women hormonal activity and the distribution of bacterial vaginosis and bacteria’s antibiotics susceptibility - Khaled M. Khleifat, Marwa Mahfoudh Khalil, Mohammad A. Al-kafaween, Moath Alqaraleh, Muhamad O. Al-limoun, Talal Salem Al-Qaisi, Husni S. Farah, Osama Nadhom Nijris, Amjad Al-Tarawneh, Haitham Qaralleh, Maha N. Abu Hajleh, Malik Amonov, Hamid A. Nagi Al-Jamal (Journal of Applied Pharmaceutical Science, 2022)
Sex hormones have a large influence on the structure and function of vaginal microbiota. A delicate balance between the vaginal microbiota and the host is one of the most important health reasons for women. The purpose of this study was to see if there were any links between female sex hormone levels and vaginal microbial diversity. A total of 100 vaginal swabs were obtained from female patients between the ages of 20 and 60 years who were suspected of having symptomatic and asymptomatic vaginal infections at the General Hospital and outpatient gynecological clinics, Samarra city, Iraq. The findings revealed that 70% and 25% of 100 high vaginal swabs with 95% positive cultures were from infected and healthy women, respectively. The most common organisms isolated belonged to Gram-negative bacteria and were Escherichia coli at 16 (16.84%) and in infected women were 9 (9.47%) and 7 (7.36%) in healthy women. The second most common isolated microorganisms from women with vaginitis were Proteus vulgaris at 8 (8.42%), Acinetobacter at 7 (7.36%), Proteus mirabilis at 7 (7.36%), and Citrobacter at 6 (6.31%). The highest percent of the isolates belonged to Gram-positive bacteria and were Staphylococcus saprophyticus at 5 (5.26%) and Staphylococcus aureus at 4 (4.21%) followed by Enterococcus faecalis at 4 (4.21%), Bacillus stearothermophilus at 3 (3.15%), Bacillus megaterium at 3 (3.15%), Enterococcus faecium at 1 (1.05%) and Leuconostoc pseudomesenteroides at 1 (1.05%), and Lactobacillus at 6 (6.31%). The greatest proportion of infection discovered in the age group 30 years was 36 (37.89%), while the least infected age group was 60 and above (2.1%). All of the bacteria that were isolatedwere susceptible to levofloxacin but resistant to metronidazole and amoxicillin-clavulanic acid. The relationship between isolated bacteria and sex hormone levels (estrogen and progesterone) revealed that sex hormone levels vary depending on the bacterial type. Burkholderia cepacia and Lactobacillus had the highest estrogen levels, while Pseudomonas fluorescens and Aeromonas had the highest progesterone levels.
Keywords: Vaginal infections, estradiol, progesterone, E. coli, S. saprophyticus